Mammary γδ T cells promote IL-17A-mediated immunity against Staphylococcus aureus-induced mastitis in a microbiota-dependent manner - Na Pan; Lei Xiu; Ying Xu; Xuemei Bao; Yanchen Liang; Haochi Zhang; Bohui Liu; Yuanyu Feng; Huibo Guo; Jing Wu; Haotian Li; Cheng Ma; et al. (iScience, 2023)
Summary: Mastitis, a common disease for female during lactation period that could cause a health risk for human or huge economic losses for animals, is mainly caused by S. aureus invasion. Here, we found that neutrophil recruitment via IL-17A-mediated signaling was required for host defense against S. aureus-induced mastitis in a mouse model. The rapid accumulation and activation of Vγ4+ γδ T cells in the early stage of infection triggered the IL-17A-mediated immune response. Interestingly, the accumulation and influence of γδT17 cells in host defense against S. aureus-induced mastitis in a commensal microbiota-dependent manner. Overall, this study, focusing on γδT17 cells, clarified innate immune response mechanisms against S. aureus-induced mastitis, and provided a specific response to target for future immunotherapies. Meanwhile, a link between commensal microbiota community and host defense to S. aureus mammary gland infection may unveil potential therapeutic strategies to combat these intractable infections.